2018
DOI: 10.1016/j.scitotenv.2017.08.271
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biotransformation products of disperse dyes with rat liver microsomes by LC-MS/MS and theoretical studies with DNA: Structure-mutagenicity relationship using Salmonella/microsome assay

Abstract: Azo dyes are known as a group of substances with DNA damage potential that depend on the nature and number of azo groups connected to aromatic rings (benzene and naphthalene), chemical properties, e.g. solubility and reactive functional groups, which significantly affect their toxicological and ecological risks. In this paper, we used in vitro models to evaluate the metabolism of selected textile dyes: Disperse Red 73 (DR 73), Disperse Red 78 (DR 78) and Disperse Red 167 (DR 167). To evaluate the mutagenic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
(69 reference statements)
2
9
0
1
Order By: Relevance
“…Thus, these results show that Disperse Red 73 possesses superior reactivity relative to the other two dyes (Table S1). This finding, in essence, brings valuable information to the fore besides being in agreement with the mutagenic effect evaluated and obtained through the use of Salmonella typhimurium (Ames test) described by Franco et al (Franco et al, 2018).…”
Section: Reactivity and Molecular Orbital Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, these results show that Disperse Red 73 possesses superior reactivity relative to the other two dyes (Table S1). This finding, in essence, brings valuable information to the fore besides being in agreement with the mutagenic effect evaluated and obtained through the use of Salmonella typhimurium (Ames test) described by Franco et al (Franco et al, 2018).…”
Section: Reactivity and Molecular Orbital Analysissupporting
confidence: 80%
“…DR 78 and DR 167 exhibited low mutagenic activity in both the absence and presence of metabolic activity (P-450). Based on the above results, the Salmonella / microsome test can be used as an important tool to predict the effects of the ingestion of azo dyes dispersed on human health, clearly indicating that the dyes can be biotransformed (Franco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The dyes and their metabolites were entirely optimized at DFT level for the subsequent PM6 semi-empirical affinity calculations with B-DNA. After that, the reaction mechanism simulation was carried out through the application of the QM/MM techniques (Franco et al, 2018). This methodology has exhibited significantly good performance in the treatment of large systems with high level of theory.…”
Section: Semi-empirical and Quantum Calculationsmentioning
confidence: 99%
“…The dyes that bear azo groups are chromophore, and are characterized by very low solubility in water. The presence of CN-and Clsubstituents in ortho position relative to nitro groups in the molecule interferes in the mutagenicity of these compounds (Franco et al, 2018). Salmonella/microsome assay (Franco et al, 2018) conducted on the TA 98 and TA 100 strains with and without liver microsomal fractions (S9) (Zbaida and Levine, 1990) indicated that DR 73 exhibited the highest mutagenicity among the dyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation